Expert Concepts in Forensic Ecology - N. V. Mikhaleva (Теория и практика судебной экспертизы, 2021)
The article addresses the existing points of view on the term “the language of forensic expertise”. The author draws attention to the fact that many forensic expert terms comprise a synthesis of legal and scientific concepts. The legal concepts contained in Chapter 26 “Environmental crimes” of the Criminal Code of the Russian Federation, and the definitions of some of them are analyzed. It is pointed out that a range of expert notions necessary for forensic purposes is defined by the GOST R 58081-2018 “Forensic environmental expertise. Terms and definitions”, including the concepts of “environmental harm”, “damage caused to an environmental object”. They should be gradually implemented into the practice of conducting forensic environmental investigations.